Analisis Dampak Investasi Infrastruktur terhadap Kinerja Bandara dan Pertumbuhan Ekonomi - Avrilla Kuswardani; Maya Hamidah; Muhammad Faqih Zamani; Saridawati (AKUNTANSI 45, 2025)
This study uses a method of literature study (library research) that relies on secondary sources in the form of scientific journals, research reports, and relevant statistical data. This method was chosen because it is appropriate to analyze the relationship between infrastructure investment and airport performance and economic growth based on theoretical studies and historical data. In addition, a descriptive quantitative approach is used to process and analyze statistical data on infrastructure investment, passenger volume, aircraft movements, and related economic indicators. The government is investing in the development of Soekarno Hatta airport infrastructure in the form of terminal revitalization and runway 3 construction, due to an increase in passenger numbers every year and a load factor. This investment is effective in significantly increasing the capacity of the number of passengers and the quality of airport services. The revitalization of terminals 1, 2 and 3 of Soekarno Hatta airport is effective in reducing the density of passenger queues and increasing comfort for airplane passengers. The construction of runway 3 was also effective in reducing the aircraft queue from the previous 6-9 aircraft to an average of 3 aircraft. The construction of runway 3 improved the airline's on-time performance (OTP). With this improvement, not only the operational performance, passenger numbers and airport revenues are increasing, but also better connectivity, smooth distribution of goods and people, and a broad positive impact on the sustainable growth of the national economy.